CORRELATION BETWEEN PROSTATIC URETHRAL ANGLE WITH CLINICAL PARAMETERS AND BOO IN LUTS ASSOCIATED WITH BPH - Santoso, Kristian Yoci Santoso Yoci; Soebadi, Doddy M.; Djatisoesanto, Wahjoe; Budiono, Budiono (Indonesian Journal of Urology, 2013)
Objective: We investigated the correlation of the PUA on clinical parameters and bladder outlet obstruction (BOO) in men with lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH). Material & Method: This study was performed between January to April 2011. A cross sectional analysis of 24 men with LUTS associated BPH aged > 50 years was performed. Patients underwent evaluation including International Prostatic Symptom Score (IPSS), transrectal ultrasonography, uroﬂowmetry, and pressure-ﬂow study. Statistical analysis was performed to evaluate correlation of the PUA on clinical parameters and bladder outlet obstruction (BOO). Results: A total of 24 patients, aged 51 to 78 years were enrolled in this study. The mean value of total IPSS, prostate volume, PUA, and Qmax was 22 (range 7-35), 34,4 cm3 (range 21–70 cm3), 37,3° (range 25°–55°), and 10,5 mL/s (range 4,2–17,9 mL/s), respectively. Pearson’s correlation analysis showed that PUA was not signiﬁcantly correlated with IPSS (p = 0,117), Qmax (p = 0,434), total prostate volume (p = 0,213). Patients with increased PUA (PUA > 35°) had higher incidence and degree of BOO (p < 0,05). Conclusion: PUA may be one method to assess the presence of BOO in men with LUTS associated BPH. Our investigation suggest that PUA may help in the treatment of individuals by better predicting their likely classiﬁcation from a pressure-ﬂow study.Keywords: Prostatic urethral angle, benign prostatic hyperplasia, lower urinary tract symptoms, bladder outlet obstruction.